ANALISIS IMPLEMENTASI PENGENDALIAN INTERNAL TERHADAP RISIKO THEFT OF CASH SIKLUS PENDAPATAN - Rhosalina Damayanti; Ajeng Ayu Selva Mutiara Dewi; Nehemia Vedryan Ardhito; Febrianti Kartikaningrum; Nandha Victoria Panggabean; Dionisius Adita Putra (Jurnal Ekonomi dan Bisnis (EK&BI), 2021)
Public organizations are expected to be able to manage their resources with adequate internal controls, to suppress the increase in cases of corruption due to misuse of assets. This research is a qualitative descriptive research conducted at GKI Tegalrejo Salatiga by collecting primary data from interviews with informants. The information obtained then processed by data reduction techniques, data presentation, and drawing conclusions. The results show that there is still a risk of theft of cash in the income cycle at GKI Tegalrejo, but it can be mitigated by controlling practices according to the concept of COSO. Some of the obstacles encountered in implementing this internal control include the church council not being fully able to understand the Tata Laksana Gereja, the absence of Standard Operating Procedures (SOP), lack of supervision on CCTV monitor, and lack of the function of the priest as a supervisor. This research is expected to be able to encourage congregational participation to assess the practice of internal control at GKI Tegalrejo Salatiga, serve as evaluation material for the GKI Tegalrejo Salatiga council to improve its internal control, and for academics, it is hoped that this research can become a reference in developing next researches.